Synthesis And Characterization Of Nickel Nanoparticles Via Polyol Method For Biomedical Application - Nik Roseley, Nik Roselina (2011)
The diverse potential applications of nickel (Ni) nanoparticles especially in biomedical has driven intense research interest towards fully understanding the synthesis process. The aim of this work is to produce Ni nanoparticles with spherical shape and smooth surface, narrow in size distribution that can easily be tailored, through simple and economic procedure. The process followed by Au coating for biomedical application. Most of currently reported synthesis method of Ni nanoparticles usually involved tedius, low yield, expensive and complicated process. To overcome many of the limitations, we present new approach to synthesis Ni nanoparticles utilizing polyol method in the present of hydrazine as the reducing agent and ethylene glycol (EG) as the solvent. In the process of Au coating, sodium citrate acted as the reducing agent while acid citrate as the pH controller. Assynthesized products were characterized with TEM, FE-SEM, EDX, XRD, UV-Vis, FTIR, XPS, Zeta Potential and VSM to investigate the morphology, size, structure, chemical composition, surface charge, optical property as well as the magnetic property. The results indicated that spherical FCC Ni nanoparticles with the finest size of 1.8 nm had been successfully synthesized, and the size is tuneable by extending the reaction time. UV-VIS absorption spectra analysis suggested that Ni@Au bimetallic particles were produced via redox-transmetalation process with a very broad peak at about 540 nm and size range of 26 - 40 nm. Room temperature magnetic characterization of Ni nanoparticles shows typical ferromagnetic behaviour as well as the bimetallic structure with magnetization increased from 3.5 emu/g to 19.1 emu/g for particles size mentioned above.